Comparison between mastic gum resin extract and chlorhexidine mouthwash in the prevention of biofilm formation on titanium dental implants: MGRE against S. Mutans biofilm formation around dental implants - Salaie, Ranj Nadhim (Cellular and Molecular Biology, 2023)
The biofilm formation around dental implant abutment is considered the main cause of peri-implant infection. The use of antimicrobial mouthwash might potentially reduce biofilm formation and subsequent infection. This study aimed to evaluate the antibiofilm properties of mastic gum resin extract (MGRE) against S. Mutans biofilm on the surface of titanium dental implant discs. This study used grade five (medical grade) titanium dental implant discs measuring 15 mm in diameter. The substances in the MGRE were analyzed by gas chromatography mass spectrometry (GC-MS) which found 12 detectable chemicals in MGRE. In this study, S. mutans was collected around the healing abutment of a recently placed dental implant and then cultured on titanium discs (in vitro). After bacterial growth on the titanium specimens for 24 hours, they were subjected to either chlorhexidine gluconate (CHX), (n = 6) or MGRE (n = 6). The antibacterial activity tests showed that both CHX and MGRE significantly inhibited bacterial growth compared to the negative control, the lactate production and turbidity measurements were significantly lower in MGRE and CHX compared to the control (p ≤ 0.05). Regarding the antibiofilm activity, both treatments showed significantly less turbidity in their biofilm compared to the control. Moreover, scanning electron microscopy (SEM) images showed that there were very limited adherence cells on the titanium implant discs in treatment groups, while there were confluent and attached bacterial cells in the control. The MGRE showed an antimicrobial property against S. mutans indicating that it has a potential for clinical use as a mouthwash.